2017
DOI: 10.1111/jvim.14742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum 3‐Bromotyrosine Concentrations in Dogs with Steroid‐Responsive Diarrhea and Food‐Responsive Diarrhea

Abstract: BackgroundThe clinical usefulness of serum 3‐BrY concentrations for subclassifying dogs with food‐responsive diarrhea (FRD) and steroid‐responsive diarrhea (SRD) has not been studied.Hypothesis/ObjectivesTo compare serum 3‐BrY concentrations in dogs with FRD, dogs with SRD, and healthy control dogs.Animals38 dogs with FRD, 14 dogs with SRD, and 46 healthy dogs.MethodsProspective study. Measurement of 3‐BrY concentration in serum samples was performed by gas chromatography/mass spectrometry.ResultsThere was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Dogs with CIE have increased serum 3‐BrY concentrations,106 with dogs requiring anti‐inflammatory or immunosuppressive treatment having higher serum 3‐BrY concentrations compared to dogs responding to an elimination diet 107. However, sensitivity and specificity of the serum 3‐BrY concentration to differentiate dogs with IRE or NRE from those with FRE or ARE have not been determined.…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…Dogs with CIE have increased serum 3‐BrY concentrations,106 with dogs requiring anti‐inflammatory or immunosuppressive treatment having higher serum 3‐BrY concentrations compared to dogs responding to an elimination diet 107. However, sensitivity and specificity of the serum 3‐BrY concentration to differentiate dogs with IRE or NRE from those with FRE or ARE have not been determined.…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…3,5 Recent advances in the diagnosis of CIE include the development of a 6-parameter 6 (considering the dog's attitude/activity, appetite, vomiting, feces consistency, feces frequency, and weight loss; the cumulative score can range from 0 to 18) and a 9-parameter clinical scoring system 7 (which considers the dog's attitude/activity, appetite, vomiting, feces consistency, feces frequency, weight loss, serum albumin concentration, ascites/peripheral edema, and pruritus; the cumulative score can range from 0 to 27), an endoscopic lesion score, 8 and a consensus for classifying CIE based on histopathologic criteria. 3,9 However, only a few minimally or noninvasive biomarkers of inflammation have been evaluated in dogs with CIE, [10][11][12][13][14][15][16][17][18] none of which are currently routinely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…CE can be subclassified into 3 categories: food-responsive diarrhea, antibiotic-responsive diarrhea, and steroidresponsive diarrhea. 1,15 However, dogs with CE in our study were not classified into these 3 subtypes, which is a limitation of our study. Nonetheless, the development of a less invasive modality to diagnose CE may still prove to be beneficial for early diagnosis and treatment without the need to perform an intestinal biopsy.…”
Section: Discussionmentioning
confidence: 86%
“…16 Furthermore, other studies have reported elevated serum 3-BrY concentrations in dogs with CE. 15,17 Serum markers, unlike those in fecal samples, are not specific to the GI tract. Various other markers for GI diseases, such as canine alpha 1 -proteinase inhibitor, calprotectin, N-methylhistamine, and S100A12, are measured in fecal samples to assess patients with CE.…”
Section: Introductionmentioning
confidence: 99%